The role of community identity in changing online gamers’ behavior - Kristina, Anita; Achsan, Dzakiy (C-DISC, 2024)
The purpose of this research is to determine the role of community identity on the behavior of online gamers. This research was conducted on the online gaming community X, which consists of students. The method used is qualitative phenomenology with interview data collection techniques. The research results show that the identity behavior of online gamers is determined by their community identity role. This community forms its own norms and values that are mutually agreed upon. The community also motivates the formation of gaming behavior and the intentions of each member’s behavior. The rational individual of action (gamer) is formed by a group of actions based on a community of utility, not an individual utility. Community members must force themselves to gain recognition of their group identity through many irrational acts of conformity.